Kepeloporan kewirausahaan memandu pendakian daya tarik wisata Gunung Agung, Karangasem, Bali - I Gede Mudana; I Ketut Sutama; Cokorda Istri Sri Widhari (Pusat Kajian Bali Universitas Udayana, 2017)
Erupted in 1963, Mount Agung in Selat District, Karangasem Regency, the highest mountain in Bali, was started to be mounted by trekking/climbing tourists in 1980s. Since 1990’s especially 2000s, some initiatives to serve the trekking/climbing the volcanic mountain have emerged in the surrounding villages’ people. The present study is done using a technic of qualitative data analysis. The result of study shows that Mount Agung is regarded interesting to climb not only because she has exotic beauty and challenges regarding the degree of difficulty (and the degree of danger the trekkers/climbers may face) to climb but also get some certain mythologies from her status as a sacred mountain believed by Balinese people, especially the Hindu followers. The entrepreneurship practices of the local society in Selat Village then come up not only to serve the trekking/climbing as usual but also to conserve the mountain environment and of course to keep the trekkers’/climbers’ safety since the mountain has some taboos and restrictions in relation with the trekking/climbing itself.